The Factors Affecting the Organizational Silence of the Nurses And The Other Clinical-care Providers in Turkey, - Toker, F., Korkmaz, M., Kılıç, B., Yücel, A. S., Gümüş, S., (My University, 2014)
The organizational silence of nurses, midwives, and health-care assistants who play a key role to establish the communication in the health-care team is relatively more significant when compared to other occupations. The results of organizational silence can be examined in organizational, individual and social scale. The purpose of this study is to find out the reasons of organizational silence and the relations among these reasons. In the scope of analysis, descriptive statistcs, reliability analysis, correlation analysis, ANOVA analysis and Regression analyses have been used by using PASW 18.0 package software to analyze the data gathered from 256 nurses, midwives and health-care assistants in a university hospital. In this study it has been found out that the organizational silence reasons differ according to age, education status, working year, occupation, working department and gender. It has also been determined that the administrative and organizational reasons, the fears related to work, the lack of experience, the fear of isolation and the fear of disturbing relations differ according to demographical variables. Since there is generally not a compensantion for a mistake in health-care service, to remove the damages of the reasons of organizational silence in health-care sector which is relatively more significant than the other sectors is possible when the necessary precautions are taken and the reasons are identified correctly. The relations, similarities and the differences among the sectors can be presented, if the organizational silence studies both in health-care sector and in different sectors are carried out more.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Organizational Silence; Health Care; Nurse; Clinical Care.